Sperm-borne microRNA-34c regulates maternal mRNA degradation and preimplantation embryonic development in mice - Long Cui; Li Fang; Lili Zhuang; Biwei Shi; Chao-Po Lin; Yinghui Ye (BMC, 2023)
Abstract Background Studies have shown that sperm-borne microRNAs (miRNAs) are involved in mammalian preimplantation embryonic development. In humans, spermatozoan miR-34c levels are correlated with in vitro fertilization outcomes, such as embryo quality and the clinical pregnancy and live birth rates. In rabbits and cows, miR-34c improves the developmental competence of embryos generated by somatic cell nuclear transfer. However, the mechanisms underlying the regulation of embryonic development by miR-34c remain unknown. Methods Female C57BL/6 mice (6-8 weeks old) were superovulated, and pronucleated zygotes were collected and microinjected with an miR-34c inhibitor or a negative-control RNA. The embryonic development of the microinjected zygotes was evaluated, and the messenger RNA (mRNA) expression profiles of the embryos at the two-cell, four-cell and blastocyst stages (five embryos per group) were determined by RNA sequencing analysis. Gene expression levels were verified by reverse transcription-quantitative polymerase chain reaction. Cluster analysis and heat map visualization were performed to detect differentially expressed mRNAs. Pathway and process enrichment analyses were performed using ontology resources. Differentially expressed mRNAs were systematically analyzed using the Search Tool for the Retrieval of Interacting Genes/Proteins database to determine their biological functions. Results Embryonic developmental potential was significantly reduced in zygotes microinjected with the miR-34c inhibitor compared with those microinjected with a negative-control RNA. Two-cell stage embryos microinjected with an miR-34c inhibitor presented altered transcriptomic profiles, with upregulated expression of maternal miR-34c target mRNAs and classical maternal mRNAs. Differentially expressed transcripts were mainly of genes associated with lipid metabolism and cellular membrane function at the two-cell stage, with cell-cycle phase transition and energy metabolism at the four-cell stage; and with vesicle organization, lipid biosynthetic process and endomembrane system organization at the blastocyst stage. We also showed that genes related to preimplantation embryonic development, including Alkbh4, Sp1, Mapk14, Sin3a, Sdc1 and Laptm4b, were significantly downregulated after microinjection of an miR-34c inhibitor. Conclusions Sperm-borne miR-34c may regulate preimplantation embryonic development by affecting multiple biological processes, such as maternal mRNA degradation, cellular metabolism, cell proliferation and blastocyst implantation. Our data demonstrate the importance of sperm-derived miRNAs in the development of preimplantation embryos.